Preparation method of cladding laser single crystal optical fiber
The single crystal fiber cladding is prepared by drilling technology and crystallized in rare earth ion-doped single crystal melt, which solves the problems of uneven diameter of single crystal fiber and the matching of cladding materials, and realizes efficient optical waveguide transmission and high-power laser preparation.
Patent Information
- Application Number
- CN202510009963.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has problems of uneven diameters and easy cracks when preparing single crystal fibers, and the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
A single crystal optical fiber cladding is prepared by punching technology and inserted into a rare earth ion-doped oxide or fluoride single crystal melt. The melt is filled with a capillary phenomenon and the melt is crystallized in one direction through the temperature field to form a laser single crystal core.
The uniformity of the diameter of single crystal fiber and crack resistance are achieved, the quality and optical performance of the cladding are improved, efficient optical coupling and light transmission are ensured, and the preparation of high beam quality and high power single crystal fiber lasers are promoted.
Smart Images

Figure CN119882125A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of single crystal optical fiber preparation, and in particular to a method for preparing a cladding laser single crystal optical fiber. Background Art
[0002] All-solid-state laser (LDPSSL or DPL) is a laser generating device that uses a semiconductor laser (LD) or LD array (LDA) as a pump source and solid laser material as a gain medium. It has the advantages of small size, light weight, high efficiency, stable performance, good reliability, long life, and high beam quality. With its unique performance advantages, it has shown broad application prospects in many fields such as remote sensing detection, military applications, industrial production, scientific exploration, and biomedicine. With the continuous improvement of laser performance requirements in various fields, current laser research and development is moving towards high repetition frequency, high output power, high beam quality, and high energy output. In this development trend, the gain medium, as the core element of laser technology, plays a decisive role in the overall performance of the laser. It directly affects key indicators such as the laser's output power, slope efficiency, and beam quality.
[0003] However, the current mainstream gain medium materials, such as glass fiber, slab crystal and disk crystal, all have their own limitations. Although glass fiber has optical waveguide properties, its low thermal conductivity and nonlinear effects limit its application in high-power laser output; the preparation process of slab crystal is complicated, and the improvement of beam quality and laser power is limited by thermal effects; as a gain medium, disk crystal has certain advantages, but its high assembly and adjustment accuracy, strict coupling system requirements and difficulty in heat dissipation design also limit its wide application.
[0004] As a new type of gain medium material, single crystal fiber combines the advantages of crystal and glass fiber, and has significant advantages such as high thermal conductivity, miniaturization, easy integration, optical waveguide characteristics limiting laser mode, high melting point, high damage threshold and higher nonlinear effect threshold. It is regarded as an important material to promote the innovation and application expansion of high-power lasers. However, the preparation technology of single crystal fiber still faces many challenges.
[0005] At present, the micro-pull-down method and the laser-heated pedestal method are the main methods for preparing single-crystal optical fibers, but both methods have obvious defects. The single-crystal optical fibers prepared by the micro-pull-down method have a larger diameter and a significant fluctuation in diameter, which is difficult to meet the needs of high-power lasers; while the single-crystal optical fibers pulled by the laser-heated pedestal method have problems such as uneven diameter and easy cracking, which affects their application effect.
[0006] In addition, the cladding preparation of single-crystal optical fiber is also a key link in improving its performance. The cladding can not only couple the pump light into the optical fiber more effectively, but also limit the transmission light beam to form total reflection in the single-crystal optical fiber, thereby limiting the laser mode, ensuring the integrity of the single-crystal optical fiber and enhancing its hardness. However, existing cladding preparation methods, such as coating, magnetron sputtering, liquid phase epitaxy (LPE), ion beam etching, chemical corrosion, laser irradiation to change the refractive index, and 3D printing additive manufacturing methods, all have problems such as large differences in thermal expansion coefficient and refractive index with laser single-crystal optical fiber materials, easy breakage, difficult processing, long cycle and uneven thickness, which makes it difficult to achieve effective optical waveguide transmission, limiting the application potential of single-crystal fiber lasers in high power and high beam quality.
[0007] Therefore, developing new single-crystal optical fiber preparation technologies and cladding preparation methods to improve the performance of single-crystal optical fibers and meet the development needs of high-power lasers is an important issue that needs to be urgently addressed in the current field of laser technology. Summary of the invention
[0008] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a clad laser single crystal optical fiber, so as to solve the problems that the single crystal optical fiber prepared by the prior art method has uneven diameter, is prone to cracks, and the cladding material of the laser single crystal optical fiber does not match the single crystal optical fiber, making it difficult to achieve effective optical waveguide transmission.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a cladding laser single crystal optical fiber, characterized by comprising the following steps:
[0011] S1. Use a punching technique to punch a hole aligned with the central axis of the single crystal rod, and punch through the central axis of the single crystal rod to obtain a single crystal optical fiber cladding;
[0012] S2. Vertically insert the single crystal optical fiber cladding into the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride single crystal melt. Under an inert atmosphere, using the capillary phenomenon, the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride single crystal melt is filled with the single crystal optical fiber cladding. At the same time, by changing the temperature gradient in the temperature field, the melt is crystallized in one direction and solidified into a laser single crystal optical fiber core inside the single crystal optical fiber cladding. Finally, the cladding laser single crystal optical fiber is obtained through post-processing.
[0013] Furthermore, in step S1, the single crystal optical fiber cladding is an undoped oxide single crystal.
[0014] Furthermore, the undoped oxide single crystal includes YAG, YGG, LuAG, GAGG, YSGG, GSGG, Y2O3, Lu2O3, Sc2O3 or YScO3 single crystal optical fiber. Undoped oxide single crystal has the advantages of high melting point, high hardness, high thermal conductivity and optical isotropy.
[0015] Further, in step S2, the rare earth ion doped oxide single crystal includes Re:YAG, Re:GAGG, Re:YGG, Re:GSGG, Re:YSGG, Re:Y2O3 or Re:YScO3 single crystal; the rare earth ion doped fluoride single crystal includes Re:YLF or Re:CaF2 single crystal.
[0016] Further, the Re is Er 3+ 、Tm 3+ 、Ho 3+ 、Nd 3+ Cr 3+ 、Dy 3+ 、Ti 3+ , Yb 3+ One or more of.
[0017] Furthermore, in step S1, the outer diameter of the single crystal optical fiber cladding is 100 to 10000 μm, and the inner diameter is 20 to 1000 μm.
[0018] Furthermore, the melting point of the single crystal fiber cladding is greater than the melting point of the laser single crystal fiber core, and the two have no eutectic point and do not chemically react with each other. This can avoid the single crystal fiber cladding from melting or reacting with the core during the preparation of the core, making it impossible to prepare the laser single crystal fiber.
[0019] Furthermore, in step S1, the punching technology is to use a femtosecond laser to punch holes or to use an etching punching technology to punch holes.
[0020] Furthermore, in step S2, the concentration of rare earth ion doping in the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride crystal melt is 1 to 50 at.%.
[0021] Furthermore, the post-processing includes cooling, annealing and end surface grinding in sequence.
[0022] Furthermore, in the step S1, the single crystal ingot is grown by using a Czochralski method, a micro-pull-down method or a laser-heated susceptor method, and then obtained by cutting, grinding and chamfering techniques.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The single crystal fiber cladding prepared by the femtosecond laser drilling technology or the corrosion drilling technology of the present invention has uniform and controllable thickness, good density, high hardness and excellent optical properties. This innovative technology not only simplifies the processing process, but also significantly improves the quality of the cladding. More importantly, the cladding of the single crystal structure has a stronger heat dissipation capacity than the cladding of the glass structure, which effectively solves the thermal management problem of the laser single crystal fiber under high power operation. At the same time, the difference in thermal expansion coefficient and refractive index between the single crystal cladding and the laser single crystal fiber core is small, which ensures more efficient optical coupling and light transmission, thereby promoting the preparation of high beam quality and high power single crystal fiber lasers. In addition, the single crystal cladding design also significantly improves the optical waveguide transmission efficiency and limits the laser mode, making the laser output more stable and efficient, and the high heat dissipation efficiency and low light scattering loss of the cladding further enhance the overall performance of the laser single crystal fiber. By flexibly combining a variety of cladding materials, the present invention can meet the needs of different application scenarios and provide strong support for the preparation of high beam quality and high power single crystal fiber lasers.
[0025] 2. When preparing clad single crystal optical fiber, the present invention inserts the single crystal optical fiber cladding into rare earth ion doped oxide single crystal melt or rare earth ion doped fluoride single crystal melt, and uses the capillary phenomenon to make the melt fill the single crystal optical fiber cladding, and by changing the temperature gradient in the temperature field, the melt is crystallized in one direction and solidified into a laser single crystal fiber core inside the single crystal optical fiber cladding. The clad laser single crystal optical fiber prepared by this method has a uniform diameter, is not prone to cracks, and has better optical quality, which can further promote the preparation of high beam quality and high power single crystal optical fiber lasers. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the end face of the cladding laser single crystal optical fiber material of the present invention.
[0027] Figure 2 It is a schematic cross-sectional view of the cladding laser single crystal optical fiber material of the present invention.
[0028] Figure 3 This is a schematic diagram of the experimental device for preparing the single crystal optical fiber cladding using femtosecond laser drilling technology in the present invention.
[0029] Figure 4 This is a schematic diagram of the experimental device for preparing the single crystal optical fiber cladding using the corrosion and drilling technology of the present invention.
[0030] Figure 5 It is a schematic diagram of the structure of growing a laser single crystal optical fiber directly on the basis of a single crystal optical fiber cladding according to the present invention.
[0031] Figure numerals: 1. laser single crystal fiber core; 2. single crystal fiber cladding; 3. femtosecond laser; 4. helium-neon laser; 5. iridium crucible; 6. fixture; 7. heater; 8. laser crystal melt; 9. dropper; 10. strong acid mixed solution. DETAILED DESCRIPTION
[0032] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.
[0033] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0034] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.
[0035] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.
[0036] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.
[0037] The quantitative tests in the present invention were all repeated three times, and the results were averaged.
[0038] Example 1
[0039] The preparation method of Nd:YAG single crystal optical fiber with LuAG single crystal as cladding layer is as follows:
[0040] S1. Preparation of LuAG single crystal cladding
[0041] (1) Raw material preparation: According to the chemical formula Lu3Al5O 12 , weigh 5.0 kg of Lu2O3 and Al2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0042] (2) Czochralski growth: In a mixed gas atmosphere of 98v% N2 and 2v% O2, a LuAG crystal with a diameter of 30 mm was grown using the Czochralski method at a pulling speed of 1.5 mm / h and a rotation speed of 15 rpm. After the growth was completed, the temperature was lowered for 24 hours to ensure the crystal quality.
[0043] (3) Cutting and processing: The grown LuAG crystals are cut and chamfered to produce multiple pure LuAG crystal rods with a diameter of 1 mm.
[0044] (4) Preparation of pure LuAG single crystal cladding: The LuAG crystal rod is fixed horizontally on a displacement platform, and a He-Ne laser is used as an auxiliary light source. The high-power laser output by the femtosecond laser is used to horizontally penetrate the central axis of the LuAG crystal rod to prepare a capillary-shaped LuAG single crystal cladding with an inner diameter of 150 μm.
[0045] S2, Nd:YAG fiber core preparation (rare earth ion Nd in the fiber core 3+ Doping concentration is 1.0 at.%)
[0046] (1) Raw material preparation: According to the chemical formula Nd 0.03 Y 2.97 Al5O 12 , weigh 200 g of Nd2O3, Y2O3 and Al2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0047] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the LuAG single crystal cladding is fixed on the lifting rod by a clamp. Under vacuum conditions, N2 atmosphere is introduced and a heater is used to melt the raw materials in the crucible.
[0048] (3) Fiber core preparation: After observing that the raw material has melted, the lifting rod is given a downward speed, and the LuAG single crystal cladding is inserted into the Nd:YAG melt through the lifting rod. Due to the capillary phenomenon, the Nd:YAG melt will fill the thin tube of the LuAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 100W / h until there are floating objects on the surface of the Nd:YAG melt. During this process, as the temperature gradient in the temperature field changes, the Nd:YAG melt will unidirectionally crystallize in the LuAG single crystal cladding thin tube and solidify into a Nd:YAG fiber core with a diameter of 150μm.
[0049] S3, post-processing
[0050] (1) Cooling and annealing: After the fiber core preparation is completed, the sample is taken out after cooling for 24 hours and annealed to eliminate internal stress.
[0051] (2) End face processing: The two end faces of the Nd:YAG single crystal optical fiber with LuAG single crystal as the cladding layer are ground and polished to ensure good optical performance, thereby obtaining a cladding laser single crystal optical fiber.
[0052] The performance parameter comparison of the prepared LuAG single crystal cladding and Nd:YAG fiber core is shown in Table 1.
[0053] Table 1 Performance parameter comparison table of LuAG single crystal cladding and Nd:YAG fiber core prepared in Example 1
[0054]
[0055] As can be seen from Table 1, the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference in refractive index and thermal expansion coefficient between the two is small, which ensures more efficient optical coupling and optical transmission, and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0056] Example 2
[0057] The Yb:GAGG single crystal optical fiber with LuAG single crystal as cladding is prepared as follows:
[0058] S1. Preparation of LuAG single crystal cladding
[0059] (1) Raw material preparation: According to the chemical formula Lu3Al5O 12 , weigh 300 kg of Lu2O3 and Al2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0060] (2) Micro-pull-down growth: In a mixed gas atmosphere of 98v% N2 and 2v% O2, a φ2×250mm film was grown using the micro-pull-down method at a drop rate of 1.5mm / h. 3 After the growth is completed, the temperature is lowered for 24 hours to ensure the quality of the crystal.
[0061] (3) Cutting and processing: The grown LuAG crystal is cut and chamfered to produce two pieces with a size of φ1×100 mm. 3 Pure LuAG crystal rod.
[0062] (4) Preparation of pure LuAG single crystal cladding: The LuAG crystal rod is fixed horizontally on a displacement platform, and a He-Ne laser is used as an auxiliary light source. The high-power laser output by the femtosecond laser is used to horizontally penetrate the central axis of the LuAG crystal rod to prepare a capillary-shaped LuAG single crystal cladding with an inner diameter of 200 μm.
[0063] Preparation of S2, Yb:GAGG fiber core (rare earth ion Yb in the fiber core 3+ Doping concentration is 1.0 at.%)
[0064] (1) Raw material preparation: According to the chemical formula Yb 0.03 G 2.97 Al2Ga3O 12 , weigh 300 g of Yb2O3, Gd2O3, Al2O3, and Ga2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0065] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the LuAG single crystal cladding is fixed on the lifting rod by a clamp. Under vacuum conditions, N2 atmosphere is introduced and a heater is used to melt the raw materials in the crucible.
[0066] (3) Fiber core preparation: After observing that the raw material has melted, the lifting rod is given a downward speed, and the LuAG single crystal cladding is inserted into the Yb:GAGG melt through the lifting rod. Due to the capillary phenomenon, the Yb:GAGG melt will fill the thin tube of the LuAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 80W / h until there are floating objects on the surface of the Yb:GAGG melt. During this process, as the temperature gradient in the temperature field changes, the Yb:GAGG melt will unidirectionally crystallize in the LuAG single crystal cladding thin tube and solidify into a Yb:GAGG fiber core with a diameter of 200μm.
[0067] S3, post-processing
[0068] (1) Cooling and annealing: After the fiber core preparation is completed, the sample is taken out after cooling for 20 hours and annealing is performed to eliminate internal stress.
[0069] (2) End face processing: The two end faces of the Yb:GAGG single crystal optical fiber with LuAG single crystal as cladding are polished to ensure good optical performance and obtain cladding laser single crystal optical fiber.
[0070] The performance parameter comparison of the prepared LuAG single crystal cladding and Yb:GAGG fiber core is shown in Table 2.
[0071] Table 2 Performance parameter comparison table of LuAG single crystal cladding and Yb:GAGG core prepared in Example 2
[0072]
[0073] As can be seen from Table 2, the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference in refractive index and thermal expansion coefficient between the two is small, which ensures more efficient optical coupling and optical transmission, and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0074] Example 3
[0075] The preparation method of Er:YSGG single crystal optical fiber with LuAG single crystal as cladding is as follows:
[0076] S1. Preparation of LuAG single crystal cladding
[0077] (1) Raw material preparation: According to the chemical formula Lu3Al5O 12 , weigh 5.0 kg of Lu2O3 and Al2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0078] (2) Czochralski growth: In a mixed gas atmosphere of 98v% N2 and 2v% O2, a LuAG crystal with a diameter of 35 mm was grown using the Czochralski method at a pulling speed of 2mm / h and a rotation speed of 25rpm. After the growth was completed, the temperature was lowered for 18 hours to ensure the crystal quality.
[0079] (3) Cutting and processing: The grown LuAG crystals were cut and chamfered to produce multiple pure LuAG crystal rods with a diameter of 1.5 mm.
[0080] (4) Preparation of pure LuAG single crystal cladding: Concentrated sulfuric acid and phosphoric acid were mixed in a volume ratio of 1:1, heated to 220°C, kept at a constant temperature for 20 minutes, cooled to 180°C, and kept at a constant temperature for another 5 minutes. Then, a small amount of the strong acid mixed solution at 180°C was taken with a rubber-tipped dropper and dripped onto the center of the upper end face of the LuAG crystal rod. The above steps were repeated several times from top to bottom until the center of the crystal was corroded into a central through hole, and finally a capillary-like LuAG single crystal cladding with an inner diameter of 500 μm was prepared.
[0081] Preparation of S2, Er:YSGG fiber core (rare earth ion Er in the fiber core 3+ Doping concentration is 50.0at.%)
[0082] (1) Raw material preparation: According to the chemical formula 1.5 Y 1.5 Sc2Ga3O 12 , weigh 150 g of Er2O3, Y2O3, Sc2O3, and Ga2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0083] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the LuAG single crystal cladding is fixed on the lifting rod by a clamp. Under vacuum conditions, N2 atmosphere is introduced and a heater is used to melt the raw materials in the crucible.
[0084] (3) Fiber core preparation: After observing that the raw material has melted, the lifting rod is given a downward speed, and the LuAG single crystal cladding is inserted into the Er:YSGG melt through the lifting rod. Due to the capillary phenomenon, the Er:YSGG melt will fill the thin tube of the LuAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 90W / h until there are floating objects on the surface of the Er:YSGG melt. During this process, as the temperature gradient in the temperature field changes, the Er:YSGG melt will unidirectionally crystallize in the LuAG single crystal cladding thin tube and solidify into an Er:YSGG fiber core with a diameter of 500μm.
[0085] S3, post-processing
[0086] (1) Cooling and annealing: After the fiber core preparation is completed, the sample is taken out after cooling for 20 hours and annealing is performed to eliminate internal stress.
[0087] (2) End face processing: The two end faces of the Er:YSGG single crystal optical fiber with LuAG single crystal as cladding are polished to ensure good optical performance and obtain cladding laser single crystal optical fiber.
[0088] The performance parameter comparison of the prepared LuAG single crystal cladding and Er:YSGG core is shown in Table 3.
[0089] Table 3 Performance parameter comparison table of LuAG single crystal cladding and Er:YSGG core prepared in Example 3
[0090]
[0091] As shown in Table 3, the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference between the refractive index and thermal expansion coefficient of the two is small, which ensures more efficient optical coupling and optical transmission, and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0092] Example 4
[0093] The preparation method of Cr, Tm, Ho: YAG single crystal optical fiber with LuAG single crystal as cladding is as follows:
[0094] S1. Preparation of LuAG single crystal cladding
[0095] (1) Raw material preparation: According to the chemical formula Lu3Al5O 12 , weigh 5.0 kg of Lu2O3 and Al2O3 powder raw materials according to the stoichiometric ratio (the purity of each raw material is 99.999%).
[0096] (2) Czochralski growth: In a mixed gas atmosphere of 98v% N2 and 2v% O2, a LuAG crystal with a diameter of 35 mm was grown using the Czochralski method at a pulling speed of 1.5 mm / h and a rotation speed of 25 rpm. After the growth was completed, the temperature was lowered for 18 hours to ensure the crystal quality.
[0097] (3) Cutting and processing: The grown LuAG crystals were cut and chamfered to produce multiple pure LuAG crystal rods with a diameter of 0.7 mm.
[0098] (4) Preparation of pure LuAG single crystal cladding: The LuAG crystal rod is fixed horizontally on a displacement platform, and a He-Ne laser is used as an auxiliary light source. The high-power laser output by the femtosecond laser is used to horizontally penetrate the central axis of the LuAG crystal rod to prepare a capillary-shaped LuAG single crystal cladding with an inner diameter of 100 μm.
[0099] Preparation of S2, Cr, Tm, Ho: YAG fiber core (Rare earth ions Cr in the fiber core 3+ The doping concentration is 0.85 at.%, Tm 3+ The doping concentration is 5.9at.%, Ho 3+ The doping concentration is 0.36 at.%)
[0100] (1) Raw material preparation: According to the chemical formula Cr, Tm , Ho:Y3Al5O 12 , weigh 150 g of Tm2O3, Y2O3, Al2O3, Cr2O3, and Ho2O3 powder raw materials (the purity of each raw material is 99.999%) according to the stoichiometric ratio.
[0101] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the LuAG single crystal cladding is fixed on the lifting rod by a clamp. Under vacuum conditions, N2 atmosphere is introduced and a heater is used to melt the raw materials in the crucible.
[0102] (3) Fiber core preparation: After observing that the raw material has melted, give the lifting rod a downward speed, and insert the LuAG single crystal cladding into the Cr, Tm, Ho: YAG melt through the lifting rod. Due to the capillary phenomenon, the Cr, Tm, Ho: YAG melt will fill the thin tube of the LuAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 100W / h until there are floating objects on the surface of the Cr, Tm, Ho: YAG melt. During this process, as the temperature gradient in the temperature field changes, the Cr, Tm, Ho: YAG melt will unidirectionally crystallize in the LuAG single crystal cladding thin tube and solidify into a Cr, Tm, Ho: YAG fiber core with a diameter of 100μm.
[0103] S3, post-processing
[0104] (1) Cooling and annealing: After the fiber core preparation is completed, the sample is taken out after cooling for 22 hours and annealed to eliminate internal stress.
[0105] (2) End face processing: The two end faces of the Cr, Tm, Ho:YAG single crystal optical fiber with LuAG single crystal as cladding are polished to ensure good optical performance and obtain cladding laser single crystal optical fiber.
[0106] The performance parameter comparison of the prepared LuAG single crystal cladding and Cr, Tm, Ho:YAG fiber core is shown in Table 4.
[0107] Table 4 Comparison of performance parameters of LuAG single crystal cladding and Cr, Tm, Ho: YAG core obtained in Example 4
[0108]
[0109] As shown in Table 4, the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference between the refractive index and thermal expansion coefficient of the two is small, which ensures more efficient optical coupling and optical transmission, and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0110] Example 5
[0111] The preparation method of Nd:GAGG single crystal optical fiber with YAG single crystal as cladding is as follows:
[0112] S1. Preparation of pure YAG single crystal cladding
[0113] (1) Raw material preparation: Select the size of φ1×90mm 3 YAG square rod is used as the material rod.
[0114] (2) LHPG method: The laser heating pedestal method (LHPG) was used for preparation. The laser power was set to 50 W and the pulling speed ratio was set to 60:30. By precisely controlling the process parameters, the prepared product had a size of φ0.5×150 mm. 3 Pure YAG crystal rod.
[0115] (3) Preparation of pure YAG single crystal cladding: The obtained pure YAG crystal rod is fixed horizontally on the displacement platform, and a helium-neon laser is used as an auxiliary light source to ensure that the high-power laser output by the femtosecond laser can completely penetrate the central axis of the YAG crystal rod horizontally. Through this process, a capillary-shaped YAG single crystal cladding with an inner diameter of 100 μm is prepared.
[0116] Preparation of S2, Nd:GAGG fiber core (rare earth ion Nd in the fiber core 3+ Doping concentration is 2.0 at.%)
[0117] (1) Raw material ratio and weighing: According to the chemical formula Nd 0.06 G 2.94 Al2Ga3O 12 According to the regulations, high-purity Nd2O3, Gd2O3, Al2O3, and Ga2O3 powder raw materials were weighed according to the stoichiometric ratio to ensure that the purity of each raw material was 99.999% and the total mass was 150g.
[0118] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the YAG single crystal cladding is fixed to the lifting rod with a clamp. After evacuation, a nitrogen protective atmosphere is filled in, and the raw materials in the crucible are melted using a heater.
[0119] (3) Fiber core preparation: After observing that the raw material is completely melted, the YAG single crystal cladding is inserted into the Nd:GAGG melt by controlling the descending speed of the lifting rod. Using the capillary phenomenon, the Nd:GAGG melt fills the thin tube of the YAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 80W / h until there are floating objects on the surface of the Nd:GAGG melt. During this process, as the temperature gradient in the temperature field changes, the Nd:GAGG melt unidirectionally crystallizes and solidifies in the YAG single crystal cladding thin tube, forming a Nd:GAGG fiber core with a diameter of 100μm.
[0120] S3, post-processing
[0121] (1) Cooling and annealing: After the fiber core is prepared, the sample is cooled for 20 hours and then annealed to eliminate internal stress and improve the performance of the optical fiber.
[0122] (2) End face processing: Finally, the two end faces of the Nd:GAGG single crystal optical fiber with YAG single crystal as cladding are polished to ensure the flatness and smoothness of the end face to meet the requirements of subsequent applications, thus obtaining a cladding laser single crystal optical fiber.
[0123] The performance parameter comparison of the prepared YAG single crystal cladding and Nd:GAGG fiber core is shown in Table 5.
[0124] Table 5 Performance parameter comparison table of YAG single crystal cladding and Nd:GAGG core obtained in Example 5
[0125]
[0126] It can be seen from Table 5 that the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference in refractive index and thermal expansion coefficient between the two is small, which ensures more efficient optical coupling and optical transmission and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0127] Example 6
[0128] The preparation method of Er:YLF single crystal optical fiber with YAG single crystal as cladding is as follows:
[0129] S1|Preparation of pure YAG single crystal cladding
[0130] (1) Raw material preparation: According to the chemical formula Y3Al5O 12 The raw material composition is as follows: high-purity Y2O3 and Al2O3 powder raw materials are accurately weighed according to the stoichiometric ratio to ensure that the purity of each raw material is 99.999%, with a total mass of 280kg.
[0131] (2) Micro-pull-down growth: In N2 gas atmosphere, the micro-pull-down method was used to grow at a drop rate of 1mm / h. After 24 hours of cooling, a high-quality pure YAG crystal with a size of φ3×230mm was successfully grown. 3 . Crystal rod preparation: The obtained YAG crystal is cut, ground and chamfered to prepare two rods with a size of φ1×100mm 3 Pure YAG crystal rod.
[0132] (3) Preparation of pure YAG single crystal cladding: The pure YAG crystal rod is fixed horizontally on the displacement platform, and a helium-neon laser is used as an auxiliary light source to ensure that the high-power laser output by the femtosecond laser can completely penetrate the central axis of the YAG crystal rod horizontally. Through this process, a capillary-shaped YAG single crystal cladding with an inner diameter of 150μm is prepared.
[0133] S2, Er: YLF fiber core preparation (rare earth ion Er in the fiber core 3+ Doping concentration is 15.0 at.%)
[0134] (1) Raw material ratio and weighing: According to the chemical formula 0.15 Y 0.85 According to the provisions of F4, high-purity ErF3, YF3, and LiF powder raw materials are accurately weighed according to the stoichiometric ratio to ensure that the purity of each raw material is 99.999%, with a total mass of 300g.
[0135] (2) Raw material melting: The weighed raw materials are placed in an iridium crucible, and the YAG single crystal cladding is fixed to the lifting rod with a clamp. After evacuation, the vacuum condition is maintained and the raw materials in the crucible are melted using a heater.
[0136] (3) Fiber core preparation: After observing that the raw material is completely melted, the YAG single crystal cladding is inserted into the Er:YLF melt by controlling the descending speed of the lifting rod. Using the capillary phenomenon, the Er:YLF melt fills the thin tube of the YAG single crystal cladding. At the same time, the temperature is cooled at a cooling rate of 60W / h until there are floating objects on the surface of the Er:YLF melt. During this process, as the temperature gradient in the temperature field changes, the Er:YLF melt unidirectionally crystallizes and solidifies in the YAG single crystal cladding thin tube, forming an Er:YLF fiber core with a diameter of 150μm.
[0137] S3. Subsequent processing
[0138] (1) Cooling and annealing: After the fiber core is prepared, the sample is cooled for 20 hours and then annealed to eliminate internal stress and improve the performance of the optical fiber.
[0139] (2) End face processing: Finally, the two end faces of the Er:YLF single crystal optical fiber with YAG single crystal as the cladding layer are ground and polished to ensure the flatness and smoothness of the end face to meet the requirements of subsequent applications, thus obtaining a cladding laser single crystal optical fiber.
[0140] The performance parameter comparison of the prepared YAG single crystal cladding and Er:YLF core is shown in Table 6.
[0141] Table 6 Performance parameter comparison table of YAG single crystal cladding and Er:YLF core prepared in Example 6
[0142]
[0143] It can be seen from Table 6 that the melting point of the single crystal cladding is slightly higher than that of the single crystal core, and the difference in refractive index and thermal expansion coefficient between the two is small, which ensures more efficient optical coupling and optical transmission and solves the problem that the cladding material of the laser single crystal fiber does not match the single crystal fiber, making it difficult to achieve effective optical waveguide transmission.
[0144] The end face schematic diagram and the cross-section schematic diagram of the cladding laser single crystal optical fiber material prepared by the present invention are respectively as follows: Figure 1 , 2 As shown, it includes an internal laser single crystal fiber core 1 and an external single crystal fiber cladding 2.
[0145] The schematic diagram of the experimental device for preparing the single crystal optical fiber cladding by using femtosecond laser drilling technology in the present invention is as follows Figure 3As shown, when drilling a hole in the single crystal fiber raw material rod of the outer cladding, the single crystal fiber raw material rod is horizontally fixed on a displacement platform, a femtosecond laser 3 is placed on one side of the single crystal fiber raw material rod, and the laser of the femtosecond laser is directed toward the central axis of the single crystal fiber raw material rod, a helium-neon laser 4 is placed on the other side of the single crystal fiber raw material rod, the light source of the helium-neon laser 4 is adjusted to parallel light, and the parallel light is directed toward the central axis of the single crystal fiber raw material rod, the femtosecond laser 3 and the helium-neon laser 4 are turned on, and the central axis of the single crystal fiber raw material rod is horizontally penetrated by the high-power laser output by the femtosecond laser 3 to prepare the single crystal fiber cladding.
[0146] The schematic diagram of the experimental device for preparing the cladding of a single crystal optical fiber using the etching and drilling technology of the present invention is shown in FIG. Figure 4 As shown, a single crystal optical fiber raw material rod is placed vertically on a workbench, and a rubber-tipped dropper 9 is used to drop a strong acid mixed solution 10 toward the central axis of the single crystal optical fiber raw material rod until the central axis of the single crystal optical fiber raw material rod is completely penetrated, thereby obtaining a single crystal optical fiber cladding 2.
[0147] The structural schematic diagram of the present invention directly growing the laser single crystal optical fiber core on the basis of the single crystal optical fiber cladding is as follows Figure 5 As shown, when growing the laser single crystal optical fiber core, the iridium crucible 5 is placed in the heater 7, the raw material of the laser single crystal optical fiber core is placed in the iridium crucible 5, and the iridium crucible 5 is heated by the heater 7 to melt the raw material of the laser single crystal optical fiber core to obtain a laser crystal melt 8; the clamp 6 is fixed to one end of the single crystal optical fiber cladding 2, and then a downward force is applied to the clamp 6 to insert the single crystal optical fiber cladding 2 into the laser crystal melt 8, and the capillary phenomenon is used to make the laser crystal melt 8 fill the single crystal optical fiber cladding 2, and at the same time, by changing the temperature gradient in the temperature field, the melt is crystallized in one direction and solidified inside the single crystal optical fiber cladding 2 to form a laser single crystal optical fiber core 1, and then the cladding laser single fiber is obtained through cooling, annealing, and end face polishing.
[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a cladding laser single crystal optical fiber, characterized in that: The following steps are involved: S1. Use a punching technique to punch a hole aligned with the central axis of the single crystal rod, and punch through the central axis of the single crystal rod to obtain a single crystal optical fiber cladding; S2. Vertically insert the single crystal optical fiber cladding into the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride single crystal melt. Under an inert atmosphere, using the capillary phenomenon, the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride single crystal melt is filled with the single crystal optical fiber cladding. At the same time, by changing the temperature gradient in the temperature field, the melt is crystallized in one direction and solidified into a laser single crystal optical fiber core inside the single crystal optical fiber cladding. Finally, the cladding laser single crystal optical fiber is obtained through post-processing.
2. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: In the step S1, the cladding of the single crystal optical fiber is an undoped oxide single crystal.
3. The method for preparing the cladding laser single crystal optical fiber according to claim 2, characterized in that: The undoped oxide single crystal includes YAG, YGG, LuAG, GAGG, YSGG, GSGG, Y2O3, Lu2O3, Sc2O3 or YScO3 single crystal optical fiber.
4. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: In step S2, the rare earth ion doped oxide single crystal includes Re:YAG, Re:GAGG, Re:YGG, Re:GSGG, Re:YSGG, Re:Y2O3 or Re:YScO3 single crystal; the rare earth ion doped fluoride single crystal includes Re:YLF or Re:CaF2 single crystal.
5. The method for preparing the cladding laser single crystal optical fiber according to claim 4, characterized in that: The Re is Er 3+ 、Tm 3+ 、Ho 3+ 、Nd 3+ Cr 3+ 、Dy 3+ 、Ti 3+ , Yb 3+ One or more of.
6. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: In the step S1, the outer diameter of the single crystal optical fiber cladding is 100 to 10000 μm, and the inner diameter is 20 to 1000 μm.
7. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: The melting point of the single crystal optical fiber cladding is greater than the melting point of the laser single crystal optical fiber core, and the two have no eutectic point and do not chemically react with each other.
8. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: In the step S1, the punching technology is to use a femtosecond laser to punch holes or to use an etching punching technology to punch holes.
9. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: In the step S2, the concentration of rare earth ion doping in the rare earth ion-doped oxide single crystal melt or the rare earth ion-doped fluoride crystal melt is 1 to 50 at.%.
10. The method for preparing the cladding laser single crystal optical fiber according to claim 1, characterized in that: The post-treatment includes cooling, annealing and end surface grinding in sequence.
Citation Information
Patent Citations
Preparation method of embedded lithium niobate or lithium tantalate single crystal core optical fiber and single crystal core optical fiber
CN106980152A
Doped monocrystal multi-core optical fiber and preparation method thereof
CN107151092A
Method for growing crystal optical fiber core in crystal cladding layer
CN108456926A
Rare earth doped YAG crystal core-glass cladding composite optical fiber and preparation method thereof
CN115180815A